Myostatin/Smad2/Smad3 pathway define a differential clinical phenotype in COPD-associated sarcopenia - Adriana Núñez-Robainas; Maria Guitart; Adrián López-Postigo; Antonio Sancho-Muñoz; Esther Barreiro (ERJ Open Research)
Background Sarcopenia, defined as the loss of muscle mass and function, represents one of the most relevant comorbidities in patients with COPD even at early stages. We hypothesised that sarcopenia defines a specific clinical phenotype in COPD irrespective of respiratory disease severity. Markers of myostatin/Smad2/Smad3 and IGF-1/PI3K/Akt may be differentially expressed in the vastus lateralis (VL) of patients with COPD-associated sarcopenia. Methods In muscle specimens from VL, markers of the myostatin/Smad2/Smad3, Smad4 and IGF-1/PI3K/Akt pathways were evaluated (real-time PCR and immunoblotting) and correlations between clinical and biological variables of patients with sarcopenia (n=23), without sarcopenia (n=18) and healthy controls (n=13) were examined. Results In the VL of sarcopenic COPD patients, expression levels of myostatin, Smad2/Smad3 and Smad4 increased compared with those in nonsarcopenic patients and healthy controls. In sarcopenic limb muscles of patients with COPD, the myostatin Smad2/Smad3 pathway was differentially activated from patients without sarcopenia and healthy controls. Among sarcopenic patients, myostatin and p-Smad3/Smad3 levels negatively correlated with fat-free mass index (r=−0.727, p=0.026 and r=−0.703, p=0.035, respectively), myostatin and Smad4 levels correlated with quadriceps strength (r=−0.886, p=0.003 and r=−0.431, p=0.040, respectively) and myostatin correlated with diffusion capacity (r=−0.781, p=0.022). Remarkable negative correlations were observed between clinical parameters related to body composition and quadriceps muscle strength and levels of the myostatin Smad2/Smad3 pathway, suggesting its implication in the process of muscle atrophy in COPD. IGF1 gene expression was also upregulated in the VL of sarcopenic patients. Conclusion Collectively, these findings offer a potential therapeutic target in COPD-associated sarcopenia.